PROGRADE RAYLEIGH-WAVE MOTION IN THE VALLEY OF MEXICO - Malischewsky Auning P.G.; Lomnitz C.; Wuttke F.; Saragoni R. (My University, 2006)
A theory of prograde particle motion of Rayleigh waves for a layer over a half-space is derived and compared with observations in the valley of Mexico. We compute synthetic seismograms for a simplified model of the Texcoco site. The earthquake of 19 September 1985, M 8.1, featured prograde motion of Rayleigh waves within a specific frequency band. The critical parameters for the existence of prograde motion are Poisson's ratio in the layer and the shear-wave contrast between the layer and the half-space. For high values of these parameters the range of frequencies featuring prograde motion falls approximately between the site frequency and twice the site frequency. Particle motion can provide additional constraints for the inversion of surface-wave observations and H/V studies.
Keywords: PROGRADE PARTICLE MOTION; RAYLEIGH WAVES; VALLEY OF MEXICO